Combination of adsorption/desorption and photocatalytic reduction processes for PFOA removal from water by using an aminated biosorbent and a UV/sulfite system - Ren, Zhongfei; Bergmann, Ulrich; Uwayezu, Jean Noel; Carabante, Ivan; Kumpiene, Jurate; Lejon, Tore; Leiviskä, Tiina (Environmental Research, 2023)
Per- and polyfluoroalkyl substances (PFAS) are stable organic chemicals, which have been used globally since the 1940s and have caused PFAS contamination around the world. This study explores perﬂuorooctanoic acid (PFOA) enrichment and destruction by a combined method of sorption/desorption and photocatalytic reduction. A novel biosorbent (PG-PB) was developed from raw pine bark by grafting amine groups and quaternary ammonium groups onto the surface of bark particles. The results of PFOA adsorption at low concentration suggest that PG-PB has excellent removal efficiency (94.8%–99.1%, PG-PB dosage: 0.4 g/L) to PFOA in the concentration range of 10 μg/L to 2 mg/L. The PG-PB exhibited high adsorption efficiency regarding PFOA, being 456.0 mg/g at pH 3.3 and 258.0 mg/g at pH 7 with an initial concentration of 200 mg/L. The groundwater treatment reduced the total concentration of 28 PFAS from 18 000 ng/L to 9900 ng/L with 0.8 g/L of PG-PB. Desorption experiments examined 18 types of desorption solutions, and the results showed that 0.05% NaOH and a mixture of 0.05% NaOH + 20% methanol were efficient for PFOA desorption from the spent PG-PB. More than 70% (>70 mg/L in 50 mL) and 85% (>85 mg/L in 50 mL) of PFOA were recovered from the first and second desorption processes, respectively. Since high pH promotes PFOA degradation, the desorption eluents with NaOH were directly treated with a UV/sulfite system without further adjustment. The final PFOA degradation and defluorination efficiency in the desorption eluents with 0.05% NaOH + 20% methanol reached 100% and 83.1% after 24 h reaction. This study proved that the combination of adsorption/desorption and a UV/sulfite system for PFAS removal is a feasible solution for environmental remediation. Validerad;2023;Nivå 2;2023-05-05 (hanlid); Funder: Regional Council of Lapland; Troms og Finnmark County Municipality Sustainable management of PFAS-contaminated materials